Ocular injectable treatment options for postcataract macular edema: systematic review. Issue 10 (October 2022) - Ahmadyar, Gina; Hansen, Ryan
Abstract : Available literature on ocular injectable treatments for postcataract macular edema have moderate to high degrees of bias, highlighting an area for future research to determine their place in therapy. Abstract : The incidence of pseudophakic cystoid macular edema (PCME) ranges from 0.1% to 20% and is the most common cause of postprocedure vision loss. Currently, there is no widely accepted treatment for PCME. Topical nonsteroidal anti-inflammatory drugs as drops given alone or in combination with topical corticosteroids are often used; however, there is a growing body of literature surrounding the off-label use of various ocular injectable medications. The purpose of this systematic literature review was to characterize the current evidence surrounding these treatments and conduct qualitative analysis to assess the risk for bias of each study. 18 total studies were found and evaluated to have moderate (n = 3, 17%) to high risk (n = 15, 83%) of bias. Although the growing body of real-world data favors improvements in visual acuity and anatomical outcomes with these injectable treatments, larger studies with a better study design are needed to demonstrate their role in the management of PCME.